Inter Mirifica: Dalam Semangat Konsili Vatikan II Memahami dan Mengintegrasikan Media Komunikasi Sosial dalam Karya Pastoral Gereja - Y.I. Iswarahadi (Jurnal Orientasi Baru, 2013)
This article tells about the role of communication media in the Catholic Church and the Churchs task in evangelization. In this arcticle the writer explains a new spirit of the Second Vatican Council as the background of Inter Mirifica. He clarifies the content of Inter Mirifica and gives some critical notes. Then he elaborates the development of communication media in todays world and how the Church responses to it. In the second part this article the writer shares his experiences to follow up the recommendation of Inter Mirifica and Popes letters on communication media by using media to evangelize people. He uses various forms of process of catecheses using media. Finally, the writes motivates the readers to reform the life of the Church, especially through new way of communiation in a new era.